EIF Equity Survey 2025 - Ewa Kolodziej; Antonia Botsari; Frank Lang; Victoria Schein (European Investment Fund (EIF), 2025)
European companies and investors are faced with exceptional market conditions, characterised by unprecedented uncertainty and heightened volatility. The regular EIF Equity Survey aims at helping to navigate through that, providing support to venture capital (VC) and private equity (PE) market players, policy makers and interested audiences on their search for information about European equity markets. This report presents the results of the latest survey wave, covering the current market situation, challenges, and expectations for the near future. By gauging fund managers' perspectives across key indicators - including fundraising, exits, valuations, new investments, and deal flow - the survey offers a comprehensive view of current market dynamics and forward-looking expectations. Moreover, this edition features an in-depth focus topic: A comparison of the market framework conditions and investment dynamics in the EU and the US. In this context, the report covers also structural issues in European equity markets.
Keywords: 330